Cucurbitacin-B instigates intrinsic apoptosis and modulates Notch signaling in androgen-dependent prostate cancer LNCaP cells - Alafnan, Ahmed; Khalifa, Nasrin E.; Hussain, Talib; Osman, Mhdia Elhadi (Frontiers in Pharmacology, 2023)
Introduction: Among numerous triterpenoids of the Cucurbitaceae family, Cucurbitacin-B (Cur-B) is being explored for its pharmacological attributes. Reports from previous studies have explicitly shown that Cur-B possesses substantial anticancer effects. The present report focuses on exploring the anticancer attributes of Cur-B against androgen-dependent PCa LNCaP cells. Methods: LNCaP cells were exposed to commercially available purified Cur-B at varying concentrations that were selected as 5, 10, 15, 20, and 25 µM for some time of 24 h to perform various experimental studies. Results: Cytotoxicity evaluation revealed that Cur-B impeded the LNCaP cell’s viability at 5 µM (p <0.05) which increased considerably at a concentration of 25 µM (p <0.001). Cur-B was also efficacious in inducing the changes within nu-clear morphology followed by a concomitant increase in the activities of key caspases including caspase-3, -8, and -9 intriguingly in a dose-dependent trend. Cur-B treatment not only resulted in the augmentation of intracellular ROS levels within LNCaP cells at 5 µM (p <0.05) but also in-creased significantly at 25 µM concentration (p <0.001). Elevation in the ROS levels was also found to be correlated with dissipated mitochondrial membrane potential (ΔΨm) which culminated in the onset of significant apoptosis at 25 µM concentration (p <0.001). Cur-B exposure also resulted in the downregulation of cyclin D1, cyclin-dependent kinase 4 (CDK4) followed by amplified levels of p21Cip1 mRNA. Importantly, exposure of Cur-B competently reduced the expression of the Notch signaling cascade which may be the plausible cause behind Cur-B-instigated apoptotic cell death and cell cycle arrest in LNCaP cells. Discussion: These observations thus, explicitly indicated that Cur-B could be plausibly further explored as potent therapeutics against androgen-dependent PCa.